2021
DOI: 10.30935/cedtech/10885
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teaching Goals and Instructional Technology Perceptions in Faculty Members’ Technology Use

Abstract: This study portrays profile uses of technology in the classroom by faculty at a school of education at a university in Central California (N = 47). First, it describes their professional uses of certain technology on a frequency scale. Second, it reports the effects of faculty's teaching philosophy and perceptions of instructional technology (IT) in their teaching practice with regards to use of technology. This study employed quantitative data analysis. The findings indicate that faculty's teaching goals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…For a teacher to deem a generated method as appropriate, there are two aspects of it that need consideration. The rst consideration is whether the generated methods achieves speci ed teaching goals [29], including those that integrate technology, as teachers view the use of technology through the prism of their teaching goals [26,30,31]. The second consideration is whether the teaching method is practical and well suited to the particular group of students [24,32].…”
Section: Pedagogical Decision-makingmentioning
confidence: 99%
“…For a teacher to deem a generated method as appropriate, there are two aspects of it that need consideration. The rst consideration is whether the generated methods achieves speci ed teaching goals [29], including those that integrate technology, as teachers view the use of technology through the prism of their teaching goals [26,30,31]. The second consideration is whether the teaching method is practical and well suited to the particular group of students [24,32].…”
Section: Pedagogical Decision-makingmentioning
confidence: 99%
“…Study has found that creative learning speeds up the learning process and enhances students' performance (Kowang et al, 2020). Furthermore, understanding the student engagement in the learning activities encourages more than just active learning is the first step toward innovative teaching (Phan et al, 2021). However, when the trainers are too focused on their content delivering in a traditional way, it will be impotent to build conceptual understanding while neglecting to apply visualizations skills among the technical employees.…”
Section: Introductionmentioning
confidence: 99%
“…As a growing number of higher education institutions attempt to meet the demands of a new generation of digital learners, faculty adoption of teaching with technology becomes a priority and a challenge (Myers, Bennett, Brown & Henderson, 2004;Phan, Paul, & Zhu, 2021. ) Higher education institutions have been funding teaching-with-technology initiatives for years, yet adoption of technology in the college curriculum has not met expectations (Weimer, 2013).…”
Section: Introductionmentioning
confidence: 99%